(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2020)
Nilotinib hydrochloride is a tyrosine kinase inhibitor approved for the treatment of chronic myelogenous leukemia was subjected to forced degradation studies and the samples were analyzed by utilizing the LCMS compatible HPLC methods. Nilotinib Hydrochloride was subjected to thermal, hydrolytic, oxidative, acidic, basic and photolytic degradation conditions as per the regulatory guidelines. The drug was degraded in oxidative, basic and acidic environments and stable in photolytic and thermal conditions. The main degradation impurity components produced through the forced degradation study were isolated for the identification and quantification in presence of these impurities in the stability studies of drug substances as well as drug products. The identified degradation components were separated by mass assisted auto-purification technique and subjected for the characterization by NMR (13C-NMR, 1H-NMR, HMBC and HSQC), HRMS and FT-IR experimentations. Degradation products obtained from oxidative, basic and acidic environments were isolated and identified by the advanced techniques as acid degradation product (DP-1) with molecular mass of 306.11 g/mol, empirical formula C17H14N4O2 with name as 4-methyl-3- (4 -(pyridine -3-yl) pyrimidin -2 -ylamino) benzoic acid. Base degradation product (DP-2) has molecular weight of 241.08 g/mol, molecular formula C11H10F3N3 with name as 3-(4-methyl-1H-imidazol-1-yl)-5-(trifluoromethyl)aniline.Oxidative degradation product (DP-3) has molecular weight of 545.18 g/mol, molecular formula C28H22F3N7O2 with name as 3-(2-(2-methyl-5-(3-(4-methyl-1H-imidazol-1-yl)-5-(trifluoromethyl)phenylcarbamoyl) phenylamino)pyrimidin-4-yl)pyridine1-oxide.